Ocorrência e flutuação populacional de ácaros associados a seringais vizinhos de fragmentos de cerrado - Demite, Peterson R.; Feres, Reinaldo J. F. (Entomological Soc Brasil, 2007)
The basic knowledge of the seasonal occurrence of mites can supply data for elaboration of programs of ecological management to be implanted with success in the future. The objective of this study was to determine the species richness and the seasonality of mites present in two areas of rubber tree crops neighboring to native areas in Itiquira, MT. Along one year, 25 quantitative samplings were accomplished in rubber tree crop neighboring to two fragments of Cerrado (Cerradao and Mata Riparia). There were registered 199,380 mites, of 48 species, belonging to 15 families. of those, 13 species are phytophagous, 18 predators and 17 mycophagous or of unknown alimentary habit. Three phytophagous species represented more than 97% of the mites collected: Phyllocoptruta seringueirae Feres (80.8%), Tenuipalpus heveae Baker (12.7%) and Calacarus heveae Feres (3.6%). Among the predators, the most abundant species were Agistemus sp., Scirula sp. and Euseius concordis (Chant). Twenty-eight species were common to both crops. The families that had the largest number of species collected in the neighboring area to Cerradao were Tydeidae (7), Tarsonemidae (6), Eriophyidae and Phytoseiidae (4), and in the area close to Mata Riparia, Tydeidae (9) and Phytoseiidae (8). The presence of vegetation near the crop should explain the great number of species of mites classified as accidental found in this study. The largest abundances and species richness occurred in the end of the rainy season and beginning of the dry season.
Occurrence and fluctuation of mite populations associated with rubber tree crop neighbor of fragments of cerrado
Keywords: Acari; mite fauna; Agroecossistema; biodiversity; Hevea brasiliensis